The In Vitro Evaluation of Wild Banana (Musa salaccensis ZOLL) as ruminant feed - Kaswari, Teja (Fakultas Peternakan Universitas Jambi, 2016)
Abstract The objective of the present study is to evaluate parts of wild banana plant as a ruminant feed through the in vitro experiment. Parts of wild banana plant (pseudostem, leaves, fronds and banana stalks) were collected from two districts in Jambi Province. Wild banana leaves have similar nutritive value to Napier grass but their dry matter percentage was less than 10% resulted less benefit for ruminant feed. The mean values for the in vitro dry matter (DM) digestibility of pseudostem, fronds, leaves and banana stalks were 35%, 33%, 26% and 40 % respectively, while the mean values for the in vitro organic matter (OM) digestibility of pseudostem, fronds, leaves and banana stalks were 40%, 42%, 34% and 48 % respectively. It can be concluded that wild banana could be potentially used in the ration of ruminants. Keywords : wild banana, nutritive value, in vitro